2003
DOI: 10.1161/01.hyp.0000056601.29613.dd
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Activation Initiates Chamber Dilatation in Concentric Hypertrophy

Abstract: Abstract-It is uncertain whether chronic ␤-adrenoreceptor (␤-AR)-activation in hypertension could initiate the progression from compensated left ventricular (LV) hypertrophy to pump dysfunction. It is also uncertain if this effect is through adverse LV remodeling (chamber dilatation with wall thinning and pump dysfunction) or intrinsic myocardial contractile dysfunction. We evaluated the effect of 5 months of isoprenaline (0.02 mg ⅐ kg Ϫ1 ⅐ d Ϫ1 ) on hemodynamics, LV wall thickness, cavity size, and interstiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 41 publications
3
55
0
Order By: Relevance
“…Prior studies have demonstrated the relatively more important role of LV dilatation in animal models of myocardial infarction (2), pressure-overload hypertrophy (23), and pressure-overload hypertrophy together with chronic adrenergic overstimulation (3,35). However, this is the first study to show that pump dysfunction induced by persistent adrenergic activation in otherwise normal hearts may occur primarily as a consequence of LV dilatation.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Prior studies have demonstrated the relatively more important role of LV dilatation in animal models of myocardial infarction (2), pressure-overload hypertrophy (23), and pressure-overload hypertrophy together with chronic adrenergic overstimulation (3,35). However, this is the first study to show that pump dysfunction induced by persistent adrenergic activation in otherwise normal hearts may occur primarily as a consequence of LV dilatation.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, in our present study, the Iso dose employed has previously been shown by us to produce minimal cardiac myocyte necrosis (35,38), data supported by findings in the present study. The dose employed by us is nevertheless sufficient to promote deleterious interstitial changes (qualitative rather than quantitative changes) upon chronic administration (3,35,38) and hence to induce LV dilatation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In these situations, it is believed that elevated levels of circulating and tissue catecholamines produce chronic stimulation of cardiac b-adrenoceptors that might result in desensitisation, downregulation and signalling abnormalities in cardiac myocytes (Castellano & Bohm, 1997;Badenhorst et al, 2003). However, little is known about the effects of chronic stimulation of b-adrenoceptors on vascular function and its endothelial modulation.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced baseline LVDP 0 in the ISO-pretreated group (Table 1) points to a decompensated LV hypertrophy (Badenhorst et al, 2003). Although recent results in pressure-overload hypertrophied hearts (Minakawa et al, 2003) suggest that this contractile failure could be also explained by the decrease in the relative level of sarcoplasmic reticu- (Boluyt et al, 1995), this question is still under dispute (Badenhorst et al, 2003;Houser and Margulies, 2003;Ward et al, 2003) (vide infra). The lack of right ventricular hypertrophy (Fig.…”
Section: Discussionmentioning
confidence: 95%